1975
DOI: 10.1073/pnas.72.3.834
|View full text |Cite
|
Sign up to set email alerts
|

D-amphetamine disaggregates brain polysomes via a dopaminergic mechanism.

Abstract: Brain polysomes are disaggregated in rats given moderate to large doses of d-amphetamine sulfate; this response is rapid in onset, lasts for at least 4-6 hr, and varies with the age of the animal. Pretreatment with a dopamine receptor blocking agent, haloperidol or pimozide, blocks the amphetamine-induced disaggregation.Rats treated with large single doses of i-dopa (a catecholamine precursor) exhibit a major disaggregation of brain polysomes (1) and a parallel decrease in the net rate of brain protein synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…30% of control activity, suggesting significant temporal and quantitative differences in the response of individual tissues to elevated temperatures. Brain glycogen levels after amphetamine administration were significantly lower under conditions of ambient temperature which resulted in more Amphetamine is one of several pharmacological agents demonstrated to cause reductions in brain protein synthesis as detected by analysis of polyribosome profiles or in vivo amino acid incorporation methods (Moskowitz et al, 1975;Widelitz et al, 1975;Holbrook and Brown, 1976;Roe1 et al, 1978). Although amphetamine can also directly inhibit in vitro translation systems (Loh et al, 1973;Baliga et al, 1976;Widelitz et al, 1976;Nowak et al, 1983), such effects require extremely high concentrations of the drug and could not account for actions on protein synthesis in vivo.…”
mentioning
confidence: 99%
“…30% of control activity, suggesting significant temporal and quantitative differences in the response of individual tissues to elevated temperatures. Brain glycogen levels after amphetamine administration were significantly lower under conditions of ambient temperature which resulted in more Amphetamine is one of several pharmacological agents demonstrated to cause reductions in brain protein synthesis as detected by analysis of polyribosome profiles or in vivo amino acid incorporation methods (Moskowitz et al, 1975;Widelitz et al, 1975;Holbrook and Brown, 1976;Roe1 et al, 1978). Although amphetamine can also directly inhibit in vitro translation systems (Loh et al, 1973;Baliga et al, 1976;Widelitz et al, 1976;Nowak et al, 1983), such effects require extremely high concentrations of the drug and could not account for actions on protein synthesis in vivo.…”
mentioning
confidence: 99%
“…It is known that a range of treatments causes a transient disaggregation of brain polysomes to monosomes and frequently a decreased incorporation of amino acid in vivo. These include excess phenylalanine (Aoki and Siegal, 1970;Taub and Johnson, 1975;Roberts and Morelos, 1976), 5-HTP (Weiss et al, 1973;Weiss et al, 1975) L-DOPA (Roe1 et al, 1974;Weiss et al, 1975) and damphetamine (Moskowitz et al, 1975;Widelitz et al, 1975). Physical treatments that result in breakdown of brain polysomes include electroconvulsive shock (Vesco and Giuditta, 1968;Wasterlain, 1972;Dunn, 1973) and intracranial hypertension (Wasterlain, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…On P40, rats received a single injection of D-amphetamine (Sigma, 15 mg/ml/kg) or saline vehicle. We used the d -amphetamine dose of Moskowitz et al, [19] that was shown to produce protein disaggregation adolescent rats but is lower than those that produce frank toxicity [27]. Each rat in a cage received the same drug treatment.…”
Section: Methodsmentioning
confidence: 99%